ANALYSIS OF THE COST OF FOREST HARVESTING FOR THE PRODUCTION OF CHARCOAL FOR IRON AND STEEL INDUSTRY - Carvalho Lana, Guilherme; Timofeiczyk Junior, Romano; da Silva, Dimas Agostinho; Malinovski, Ricardo Anselmo; Buratto, David Alexandre (Floresta, 2018)
This study aimed to analyze the production cost structure of the system of short logs, operating with the log lengths of 2.1 m, 3.7 m and 5.0 m and to determine which of the three log lengths enables a lower final cost in the production of charcoal. Data collected from a forestry company in the municipality of Paraopeba (state of Minas Gerais, Brazil) were used. An analysis of the cutting process, the transportation and the charcoal production was performed. The results showed that the hourly cost of the short log system is higher when using larger log lengths. The cost per unit quantities (cubic meters and tons) of treatments with longer logs is smaller due to its higher yield time. The system with logs of 5.0 m presents an inferior cost for the production of charcoal when compared to the same system with logs between 3.7 m and 2.1 m of length.